Development of a rapid on-site detection method for largemouth bass virus based on RPA-CRISPR/Cas12a system - Na Li; Chunmei Dai; Yuelin Mao; Yimeng Zhang; Huiyuan Yan; Huijiao Wang; Yinghui Qin; Baicheng Huang; Xinjie Wang; Lunguang Yao (Frontiers in Microbiology)
IntroductionLargemouth bass virus (LMBV), the causative agent of largemouth bass ulcerative syndrome, poses a significant economic threat to the aquaculture industry. Rapid, simple, and reliable detection methods are essential for the timely identification of LMBV infections, enabling effective prevention and control measures.MethodsIn this study, a detection platform utilizing the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 12a (Cas12a) system was developed for LMBV. CRISPR RNA (crRNA) and recombinase polymerase amplification (RPA) primers were designed to target the highly conserved region of the major capsid protein (MCP) gene. Additionally, a one-pot method and lyophilization strategy were optimized for field applications.ResultsThe RPA-CRISPR/Cas12a system achieved a sensitivity of 50 copies/reaction within 40 minutes, without requiring specialized equipment, and exhibits high specificity for LMBV. Validation with 42 clinical samples of suspected LMBV infection demonstrated 100% concordance among the RPA-CRISPR/Cas12a method, quantitative PCR and lateral flow strip assay. The one-pot method and lyophilization strategy demonstrated consistent detection results with two-step RPA-CRISPR methods in clinical sample testing, offering more convenient and stable application characteristics for on-site detection.DiscussionThis study establishes an efficient process for detecting LMBV nucleic acids in fish clinical samples, culminating in a CRISPR-based fluorescent readout, offering significant advantages for viral diagnosis and monitoring.